POSSESSION, USE AND HANDLING OF THROWING WEAPONS THAT THREATEN LIFE, BODY AND HEALTH - Portella Bruno , PNP Wilber Sabino (2023)
The study began with the objective of distinguishing weapons and projectiles, consequently, the motive force and projected force in the use of projectiles; the possession, use and handling of slingshots or huaracas, Molotov bombs and pyrotechnic material (hazelnuts) and, finally, the consequences of the use of throwing weapons. The methodology is qualitative, where interviews were conducted. The most important result shows that slingshots and Molotov cocktails are throwing weapons. It was concluded that: Slingshots, are weapons that launch projectiles, such as gland stones or lead bullets, which, when impacting against a person or infrastructure, cause death and material damage, respectively. It is a lethal weapon, and the slingshot, in the communities, is used for traditional use in dances and personal use in grazing their animals, however, it is also used to attack people and locals.